The Making of the Modern Jewish Bible How Scholars in Germany, Israel, and America Transformed an Ancient Text. (Rowman & Littlefield Publishers, Inc., 2011)
Tracing its history from Moses Mendelssohn to today, Alan Levenson explores the factors that shaped what is the modern Jewish Bible and its centrality in Jewish life today. The Making of the Modern Jewish Bible explains how Jewish translators, commentators, and scholars made the Bible a keystone of Jewish life in Germany, Israel and America. Levenson argues that German Jews created a religious Bible, Israeli Jews a national Bible, and American Jews an ethnic one. In each site, scholars wrestled withthe demands of the non-Jewish environment and their own indigenous traditions, trying to balance fidelity and independence from the commentaries of the rabbinic and medieval world.
Keywords: Bible. -- Criticism, interpretation, etc., Jewish; Bible. -- Criticism, interpretation, etc., Jewish -- Israel; Bible. -- Criticism, interpretation, etc., Jewish -- United States; RELIGION / Biblical Studies / Old Testament; RELIGION / Judaism / Sacred Writings; Electronic resource